Alcohol and Cannabis Consumption Does Not Diminish Cure Rates in a Real-World Cohort of Chronic Hepatitis C Virus Infected Patients on Opioid Substitution Therapy—Data From the German Hepatitis C-Registry (DHC-R). (March 2019) - Christensen, Stefan; Buggisch, Peter; Mauss, Stefan; Böker, Klaus HW; Müller, Tobias; Klinker, Hartwig; Zimmermann, Tim; Serfert, Yvonne; Weber, Bernd; Reimer, Jens; Wedemeyer, Heiner; ,
Background: The importance of alcohol and cannabis consumption for the effectiveness of treatment of chronic hepatitis C virus (HCV) infection with direct acting antivirals (DAAs) in people on opioid substitution therapy (OST) has not been investigated in detail. Methods: We investigated sustained virological response (SVR) rates and proportion of lost to follow-up (LTFU) between OST (n = 739) and non-OST patients (n = 7008) in the German Hepatitis C-Registry (Deutsches Hepatitis C-Register, DHC-R), which is a national multicenter prospective non-interventional real-world registry. Non-OST patients comprised patients with former/current drug use (non-OST/DU; n = 1500) and patients never consuming drugs (non-OST/NDU; n = 5508). Findings: SVR 12/24 rates (intention to treat [ITT]) in patients consuming no or less than 30 g/day (women) or 40 g/day (men) were significantly higher in non-OST/NDU (range 91%-92%) vs OST patients (range 83%-86%), mainly due to significantly higher LTFU rates in OST (range 11%-12%) compared with non-OST/NDU (range 2%-3%). In non-OST/NDU with high alcohol consumption of more than 30/40 g/day, SVR 12/24 rates (ITT) were lower (85%) but did not differ to OST (85%) with high alcohol consumption. No significant differences could be seen for SVR 12/24 in per-protocol (PP) analysis independent of alcohol consumption or amount of alcohol intake. Cannabis use did not significantly influence SVR 12/24 in ITT or PP or LTFU. Conclusions: High SVR rates could be achieved in both OST and non-OST patients irrespective of alcohol or cannabis consumption. However, LTFU is more likely in patients with current or former drug use than in patients without drug history and in patients with high alcohol consumption but occurred mainly after end of antiviral treatment (EOT), leaving a high chance for HCV elimination in these patients.